Evolving role of semaglutide in NAFLD: in combination, weekly and oral administration - Koureta, Evgenia; Cholongitas, Evangelos (Frontiers in Pharmacology, 2024)
Non alcoholic fatty disease (NAFLD) is the most common chronic liver disease that is managed in the liver departments. It seems that the prevalence of the disease is rising worldwide and as it has the same pathogenetic pathways with metabolic syndrome, treatments that target components of the metabolic syndrome seem promising for the therapy of NAFLD as well. In this review we discuss the evolving role of semaglutide, which is a glucagon-like peptide-1 receptor agonist (GLP-1 RA) that has been already approved for the treatment of type II diabetes mellitus (T2DM) and obesity.